Redefining of the concept of a migrant housemaid in Ali's Minah Tetap Dipancung - Iskarna, Tatang (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
This article explores diasporic problems faced by an Indonesian migrant housemaid working in Saudi Arabia, presented in Denny J. Ali's essay poem